Guidelines for laboratory design : Health and safety considerations - DiBerardinis, Louis J (John Wiley & Sons, 2013)
"Focuses on Environmental considerations in addition to health and safety, emphasizing environmental issues in design as well as green lab design. Contains a new section on Sustainable Design. Includes new chapters on Material Sciences and Engineering and Nanotechnology Provides updated information in all sections, especially the chapters on Animal Research and HVAC "-